2023
DOI: 10.1002/imt2.81
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of diazotrophs and arbuscular mycorrhizal fungi on soil biological nitrogen fixation after three decades of fertilization

Abstract: Biological nitrogen (N) fixation (BNF) via diazotrophs is an important ecological process for the conversion of atmospheric N to biologically available N. Although soil diazotrophs play a dominant role in BNF and arbuscular mycorrhizal fungi (AMF) serve as helpers to favor BNF, the response of soil BNF and diazotrophic communities to different long-term fertilizations and the role of AMF in diazotrophs-driven BNF are poorly understood. Herein, a 33-year fertilization experiment in a wheat-maize intercropping s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Rhodocytophaga is a genus often associated with soils with high organic matter content and high salinity [ 49 ]. Skermanella can behave as a mycorrhizal helper bacterium, occurring especially where the number of AM fungal propagules is high [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rhodocytophaga is a genus often associated with soils with high organic matter content and high salinity [ 49 ]. Skermanella can behave as a mycorrhizal helper bacterium, occurring especially where the number of AM fungal propagules is high [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Performing microbial co-occurrence ecological network analyses can enhance our understanding of complex microbial communities [24,25]. According to previous studies, various environmental factors, such as soil pH, protein, and nutrients, can affect the microbial community structure, especially in extreme environments [26].…”
mentioning
confidence: 99%
“…Soil microorganisms interacting with crops play a pivotal role in promoting crop growth, increasing yield, and enhancing resilience to abiotic stress (Figure 1). Research has indicated that soil nitrogen-fixing bacteria can enhance crop growth by immobilizing atmospheric nitrogen and engaging in mutual recognition and molecular communication with legume crops [14,20]. Conversely, crops actively recruit and shape inter-root microbial communities through root secretions including sugars, phenolics, amino acids, and ketones, which serve as nutrients for beneficial microorganisms, thereby fostering optimal conditions for crop growth [10,21].…”
Section: Functions Of Agricultural Soil Microorganisms 21 Crop Growthmentioning
confidence: 99%
“…For example, nitrogen-fixing microorganisms facilitate ammonium uptake by leguminous crops through symbiosis, while diffused ammonium enriches the surrounding soil, benefiting other microorganisms. Simultaneously, nitrifying microorganisms (such as Skermanella and Azospirillum) convert ammonium into gaseous nitrogen compounds, which are released into the atmosphere [14,27]. Phosphorus, a limiting nutrient in agricultural soils, exhibits low mobility.…”
Section: Nutrient Cycling In Agricultural Landmentioning
confidence: 99%
See 1 more Smart Citation